Earnings conservatism and audit committee financial expertise - Sultana, Nigar; Van der Zahn, J. (Wiley-Blackwell Publishing Asia, 2015)
Using an Australian sample of 494 firm-year observations, this study finds that accounting financial expertise is the primary type of expertise that influences earnings conservatism, rather than nonaccounting financial expertise. The association between accounting financial expertise and conservatism holds only when the accounting financial expert(s) on audit committees is (are) independent. Overall, results suggest that audit committee accounting financial expertise is important in recognising the asymmetrical timeliness of losses. Findings provide a better understanding of the dynamics between audit committee financial expertise and earnings conservatism and demonstrate the importance of accounting financial expertise in improving financial reporting quality.